2022
DOI: 10.1002/hbm.26163
|View full text |Cite
|
Sign up to set email alerts
|

Brain functional connectivity alterations associated with neuropsychological performance 6–9 months following SARS‐CoV‐2 infection

Abstract: Neuropsychological deficits and brain damage following SARS‐CoV‐2 infection are not well understood. Then, 116 patients, with either severe, moderate, or mild disease in the acute phase underwent neuropsychological and olfactory tests, as well as completed psychiatric and respiratory questionnaires at 223 ± 42 days postinfection. Additionally, a subgroup of 50 patients underwent functional magnetic resonance imaging. Patients in the severe group displayed poorer verbal episodic memory performances, and moderat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 119 publications
2
29
0
Order By: Relevance
“…The cognitive areas most frequently affected were executive functions and visuospatial memory, in line with other studies focusing on the long-term neuropsychological effects of COVID-19 ( Llana et al, 2022 , Hall et al, 2022 , Ferrucci et al, 2022 ). Notably, neuropsychological deficits have been associated with alterations in brain functional connectivity in a previous study ( Voruz et al, 2023 ). Most patients in our cohort had a mild disease course, as only 3/23 required hospitalization during acute COVID-19.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The cognitive areas most frequently affected were executive functions and visuospatial memory, in line with other studies focusing on the long-term neuropsychological effects of COVID-19 ( Llana et al, 2022 , Hall et al, 2022 , Ferrucci et al, 2022 ). Notably, neuropsychological deficits have been associated with alterations in brain functional connectivity in a previous study ( Voruz et al, 2023 ). Most patients in our cohort had a mild disease course, as only 3/23 required hospitalization during acute COVID-19.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, this observation remarks anatomical overlap between the olfactory and memory networks ( Insausti et al, 2002 ). Altered connectivity of subcortical structures has recently been associated with memory scores in a group of long-COVID patients (6–9 months) ( Voruz et al, 2023 ); however, in this group, the patients did not necessarily showed OD, but were rather stratified based on the hospitalization at the time of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…A comparatively small number of dynamic investigations limited to FDG‐PET, have evaluated metabolic abnormalities while simultaneously assessing neuropsychological symptoms in COVID infection 7,8 . These studies suggested a significant correlation between frontoparietal hypometabolism and cognitive scores in post‐COVID patients 8 a finding confirmed with by a few functional magnetic resonance imaging (fMRI) COVID studies 8,9 that revealed critical functional connectivity patterns in major functional networks (DMN and DAN) associated with impaired cognition. However, these studies either lacked a control group or else assessed connectivity differences only among COVID patients at different disease stages.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, olfactory dysfunctions are present in, and often precede, neurodegenerative disorders, such as Alzheimer's and Parkinson's disease 21 , autism, where social cognition is affected 17 , and in depression, where mood is affected 22 . At the same time, emotional and cognitive deficits are shown by patients with olfactory dysfunction even several months after experiencing mild, moderate, or severe COVID-19 disease 20,23 . Therefore, emotional and cognitive well-being might be affected by olfactory dysfunction.…”
Section: Introductionmentioning
confidence: 99%